Accountancy Internship Program of a State University in the National Capital Region - Roque, Ryan C.; Conejos, Moirla Dawn Hillary C.; Cusi, Valerie Joy M.; Yasto , John Lloyd D. (International Journal of Psychosocial Rehabilitation, 2020)
Student Internship Program in the Philippines, the revise guideline issued by the Commission on Higher Education, ensures better quality of their students’ learning and exposure as well as safety during the internship period. With this, the researchers conducted this study to evaluate the level of effectiveness of accountancy internship program implemented by a State University in the National Capital Region from internship plan, and internship proper up to monitoring and evaluation. In this research, descriptive method was used. Survey questionnaires were distributed to the 111 graduating accountancy students in the academic year 2019-2020. Results revealed that the accountancy internship program of the State University is effective in terms of all the aspects. Recommendations made by the researchers include discussion with the students and parents about the provision in the insurance taken, a ratio of one (1) section only per accounting professor to provide better guidance and assistance. The results could serve as guide to state universities and colleges (SUCs) that will implement the internship in accountancy program for the first time.